2009
DOI: 10.1007/s10557-009-6186-3
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Improves Endothelial Function and Cardiac Performance in Patients with Dilated Cardiomyopathy: The Role of Inflammation

Abstract: Twelve weeks of treatment with atorvastatin significantly decreased serum sICAM-1, CRP and vWF levels, and improved the FMD, LVEF and 6MWT outcomes. Inhibition of inflammation, alleviating endothelium damage and endothelial dysfunction might comprise part of the underlying mechanisms leading to the improvement of LV function and exercise tolerance in patients with IDCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 27 publications
(27 reference statements)
1
18
1
1
Order By: Relevance
“…Dilated cardiomyopathy (DCM) [1,2] is a primary chronic myocardial disease manifesting with systolic dysfunction which is not due to pericardial disease, coronary artery disease, hypertension, congenital heart disease, or valvular heart disease [3]. The diagnosis of DCM requires excluding the above listed etiologic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Dilated cardiomyopathy (DCM) [1,2] is a primary chronic myocardial disease manifesting with systolic dysfunction which is not due to pericardial disease, coronary artery disease, hypertension, congenital heart disease, or valvular heart disease [3]. The diagnosis of DCM requires excluding the above listed etiologic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial infarction (MI) is a common presentation of CVD (Liu et al 2009). Some clinical trials established the benefits of statins after MI.…”
Section: Introductionmentioning
confidence: 99%
“…Statins were reported to improve the endothelial function by mechanisms that are unrelated to a cholesterol-lowering effect. Some of these mechanisms involve prevention of inflammation, down-regulation of systemic inflammatory responses (Liu et al 2009) and induction of angiogenesis (Hamelin and Turgeon 1998). In a previous study, therapy with pravastatin was found to decrease the risk of recurrent coronary events after MI in patients with average cholesterol levels; this outcome may have resulted in part from anti-inflammatory as well as lipid-lowering properties of the drug (Ridker et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Aumento de sICAM-1 pode ser uma consequência indireta de danos do tecido ou da inflamação (TEPPO et al, 2001). Em indivíduos sem manifestações clínicas de patologia cardiovascular, a sICAM-1 parece ser o melhor marcador de lesão endotelial (LIU et al, 2009).…”
Section: Introductionunclassified